Vintilă Ciocâlteu (1891-1947): physician, biochemist, poet and professor - Popescu, Mihai; Nicolescu, Raluca (Medicine and Pharmacy Reports, 2013)
Among the ambassadors of Romanian science and culture, we include the doctor Vintilă Ciocâlteu. Along with Victor Babeş, Nicolae Paulescu and George Emil Palade, Vintilă Ciocâlteu contributed further, by the reagent which he prepared together with Otto Folin, to the completion and deepening of the knowledge of cell biology within the medical agricultural, horticultural research or industrial chemistry. A multi-faceted personality, V. Ciocâlteu was also a remarkable poet, who entered into an unjust and hopeless conflict with the communist regime. Just like many of his compatriots, he was deleted from medical or literature books, was expelled from the department of Medicine in Bucharest and was charged with offences that he did not commit. But his name could not be deleted from the laboratory methods which used - the Reagent Folin-Ciocâlteu! Today, doctor Vintilă Ciocâlteu continues to promote the fame of the Romanian medicine in the world.